CHORIORETINAL WHITE DOT LESIONS IN EYES WITH MULTIFOCAL CHOROIDITIS AND TILTED DISK SYNDROME WITH INFERIOR STAPHYLOMA. Issue 1 (January 2017) - Astroz, Polina; Mrejen, Sarah; Souied, Eric H.; Jung, Camille; Cohen, Salomon Y.
Abstract : Purpose: To assess the influence of tilted disk syndrome (TDS) and inferior staphyloma on the macular clinical expression of MFC. Methods: Medical charts of patients with MFC examined since 2009 were reviewed retrospectively. All patients underwent standard examination and multimodal imaging including fundus color photography, fundus autofluorescence, and spectral domain optical coherence tomography. Two groups of patients were compared : Group 1 with TDS and inferior staphyloma and Group 2 without. The number of MFC spots were counted and normalized to the surface area in a circle centered about the fovea. In Group 1, the number of lesions inside the staphyloma was compared with that outside the staphyloma. Results: At baseline, 8 eyes in Group 1 had a mean (±SD) higher number of chorioretinal lesions outside the staphyloma (14.5 [±7.2]) than within the staphyloma (5 [±5.5]) ( P = 0.017). All 11 eyes in Group 2 had chorioretinal lesions homogeneously distributed in the posterior pole. Eyes with TDS and inferior staphyloma developed choroidal neovascularization more frequently (6/8 eyes) than eyes without TDS (5/11 eyes) ( P = 0.026). Conclusion: Inferior staphyloma associated with TDS could modulate the clinical expression of the inflammatory and neovascular process in eyes with MFC. Abstract : In this retrospective case series including 19 eyes with multifocal choroiditis (MFC), localization of chorioretinal spots in 8 eyes with and 11 eyes without tilted disk syndrome and inferior staphyloma were analyzed. Lesions were located predominantly outside the staphyloma, suggesting an influence of tilted disk syndrome with inferior staphyloma in the clinical expression of MFC.